Sistem Pendukung Keputusan Untuk Menetukan Jenis Perawatan Wajah Menggunakan Metode AHP dan SAW - Reni Lestari; Raissa Amanda Putri (Journal of Information System Research (JOSH), 2023)
Currently, facial care is highly desired by society, especially for women in this world. Problems with the face can be caused by unsuitable care products used because they don't know the problems with each individual face. One of the treatments that can be done is at the Putri Ms Glow store, where we can ask for solutions or good consultations in dealing with problems on each patient's face. Given these problems, it is necessary to create or design a web-based Decision Support System using the AHP and SAW methods. The existence of the AHP and SAW methods can be expressed as a comparison that can make it easier to calculate a ranking weight between alternatives. In order to make it easier for patients to carry out consultations or treatment, the design of this web application was carried out using a system that was designed or a system that is currently running, where data is obtained from the results of observations or interviews in order to determine criteria and alternatives in making decisions for Putri Ms Glow. After the data is collected, weighting calculations are carried out from AHP and after that they are ranked using SAW to determine which patients are prioritized first. Based on the results of research and calculations that have been tested using the AHP method, it helps weight alternatives and criteria with a weight scale of 1-9 , after the weighting was carried out, the ranking was carried out using the SAW method to get the final score, rank 1 was obtained by Resti with a final score of 1.0067 and rank 15 was obtained by Suci with a final score of 0.5633. The before, it is the priority for Resti to get treatment first.